Avascular Necrosis after Oral Corticosteroids in Otolaryngology: Case Report and Review of the Literature. Issue 1 (March 2016) - Kennedy, Patrick; Bassiouni, Ahmed; Psaltis, Alkis; Antisdel, Jastin; Brunworth, Joseph
Objective: In this report, we present a rare case of avascular necrosis (AVN) in an otherwise healthy 42-year-old male patient treated with low dose oral corticosteroids for his bronchitis. A systematic review of the literature related to AVN and corticosteroids was performed. Case Report: Forty-two-year-old male with no underlying conditions predisposing him to AVN who had been treated four years before for chronic bronchitis with two courses of oral prednisone therapy presented with bilateral AVN of the hips. Methods: An OVID database search of the terms "low total dose, " "corticosteroids, " and "avascular necrosis" was performed. Two PubMed searches of various permutations of "low-dose, " "corticosteroids, " "avascular necrosis, " and "osteonecrosis" were also performed. Results were then narrowed to relevant articles. Results: Median total dose of oral corticosteroids in patients with AVN in reviewed articles was 981 mg, with lowest reported association at 105 mg. Median duration of therapy was 16 days with shortest course of six days. Conclusion: There is emerging data linking AVN with corticosteroid doses previously thought to be safe. After reviewing the relevant literature, it is our consensus to inform all patients regarding AVN before oral corticosteroid use.